Early Failure of Total Ankle Arthroplasty in a Patient with Ipsilateral Varus Knee Deformity - Taehyeon Kim; Su Chan Lee; Chang Hyun Nam; Suengryol Ryu; Hye Sun Ahn; Ji-Hoon Baek (Case Reports in Orthopedics)
Multiple risk factors such as age, body mass index (BMI), preoperative diagnosis, smoking, diabetes mellitus, malalignment of an implant, and presence of ipsilateral hindfoot fusion have been shown to contribute to failure of total ankle arthroplasty (TAA). However, the exact causes of TAA failure remain uncertain, and various causes can lead to a need for revision surgery. We report a case of early aseptic loosening of the implant following TAA in a patient with severe varus deformity of the ipsilateral knee.